Incorporation of Culture in the Science Classroom - Guthrie, Mariah (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
Few science classrooms incorporate an understanding of the effects of culture into the way science is taught. Yet few minority students continue onto careers in hard sciences, and the methods of instruction of these courses throughout primary and secondary years may be contributing to this. With the rising recognition of and respect for diversity within classrooms across the country, the teaching styles of many schools need to be revised to recognize and account for the cultures which students bring with them into the classroom. The practice of culturally inclusive instruction for all students is called Culturally Responsive Pedagogy (CRP). Culture is central to learning. It plays a role not only in communicating and receiving information, but also in shaping the thinking process of groups and individuals. For this reason, Culturally Responsive Pedagogy is necessary if we wish to include all students in science education.